2014
DOI: 10.1039/c4cp01341g
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the degradation mechanism of rechargeable lithium/sulfur cells: a comprehensive study of the sulfur–graphene oxide cathode after discharge–charge cycling

Abstract: Degradation mechanism of rechargeable lithium/sulfur-graphene oxide cell was studied using scanning electron microscopy and X-ray spectroscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
106
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 117 publications
(113 citation statements)
references
References 56 publications
(77 reference statements)
5
106
0
Order By: Relevance
“…Notably, the peak intensity from 171.1 to 165.0 eV assigned to polythionate (≈168.2 eV) and thiosulphate(≈167.2 eV), respectively becomes much stronger, while the peaks corresponding to active S species with C—S bond and O—S bond from 164.0 to 160.0 eV have weakened. The result indicates that some of the active S species has been converted into the polythionate and thiosulphate during cycling 48. The as‐formed polythionate and thiosulphate species during cycling can serve as highly efficient polysulfide mediator to limit the diffusion of lithium polysulfides, which is confirmed by recent report 49…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…Notably, the peak intensity from 171.1 to 165.0 eV assigned to polythionate (≈168.2 eV) and thiosulphate(≈167.2 eV), respectively becomes much stronger, while the peaks corresponding to active S species with C—S bond and O—S bond from 164.0 to 160.0 eV have weakened. The result indicates that some of the active S species has been converted into the polythionate and thiosulphate during cycling 48. The as‐formed polythionate and thiosulphate species during cycling can serve as highly efficient polysulfide mediator to limit the diffusion of lithium polysulfides, which is confirmed by recent report 49…”
Section: Resultssupporting
confidence: 70%
“…All the capacity retention and capacity degradation are calculated from the third cycle after achieving stabilized capacity. The achieved cycling ability in Figure 5c,d is much better than that of most previous reports 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 48. Only very recently, Cui and co‐workers51 successfully demonstrated that the TiO 2 /S yolk–shell composites can be cycled over 1000 times with a capacity decay of 0.033% per cycle.…”
Section: Resultsmentioning
confidence: 53%
See 3 more Smart Citations